Approaching linguistic semiosis biologically: implications for human evolution - Kravchenko, Alexander (Rivista Italiana di Filosofia del Linguaggio, 2022)
As a functional feature of our species, language, it is argued, cannot be understood outside the domain of biological organization. The established view of language as a tool used for communication has little to offer towards a better understanding of the nature and function of language, making it external to human biology and accounting for the language–mind dichotomy entrenched in philosophy of language and mainstream cognitive science. By contrast, biosemiotics, an interdisciplinary paradigm for the study of life as semiosis, attempts to overcome this epistemological inconsistency by positing the biological nature of signs. At the same time, the theoretical framework of biosemiotics is marked by a conceptual tension between the physicalist accounts of symbol often used in biosemiotics and the Peircean notion of symbol as a kind of sign in the semiotic hierarchy of iconic, indexical, and symbolic reference; this hierarchy is essential in understanding linguistic semiosis as a major evolutionary transition rather than a cultural invention. The firmly established belief that, evolutionarily, sapience precedes language impedes our understanding of language as human life in semiosis; such an understanding becomes possible with a systems approach to the study of our species.As situationally driven embodied interactional behavior, languaging is constitutive of the human organism-environment system as a unity. Linguistic semiosis – the development of the ability to orient others and self in their consensual domain to what is not perceptually present – is a biological adaptation that allows humans to be able to better live in their habitat and sets them apart from the rest of the living world as linguistic organisms capable of operating on first-order abstractions in co-ordinations of interactional behavior. It is hypothesized that the emergence of language was the pivoting point in the evolution of the human brain, laying the basis for abstract thought as neuronal processes that lead to the establishment of second-order consensuality and languaging as behavior in a second-order consensual domain: cognition as a biological function met language as a biological adaptation, and the ontogenesis of Homo sapiens began.